Psychological characteristics of younger and older coaches - Dimec, T.; Kajtna, T. (Kinesiology, 2009)
A coach is a key to developing an athlete`s career and one of the most important factors in his/her success. The career of a coach is a stressful one, it requires a lot of work and dedication, and a great amount of involvement. The goal was to find any differences that might arise between coaches who were in this profession for a longer time and were thus older and those who worked as coaches for a shorter period of time. We assumed that such differences occur in coaches due to the stressfulness of the occupation. Our hypothesis was confirmed by the results obtained on the sample of 275 Slovene coaches. The group of younger coaches consisted of those who were up to 34 years old, whilst the older coaches were 35 years of age or older. Their personality traits, social skills, leadership styles, achievement motivation and self-motivation, emotional competences and attitudes were measured. The younger coaches are more accurate, more open to novelties, more conscious, more agreeable and they know how to manage their emotions better. The older coaches behave in a more democratic manner, but they more frequently behave autocratically as well. The older coaches report more frequently that working as a coach is a source of problems for them.